La valeur aspectuelle – problème de traduction (Confrontation franco-tchèque) - Sládková, Miroslava (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
The aspect quality – a translation problem (French-Czech confrontation) This article is a refl ection on the problem of verbal aspect in Czech and in French and on related translation problems. Czech verbs have a binary opposition of perfectivity versus imperfectivity; in French the situation is more complex, where the nature of the verbal action (Aktionsart) usually comes into play. In Slavonic langua ges aspect and temporality features differ; in French the temporal information prevails. The problem arises when the translator must respond to the relevant aspect opposition in Czech. It would be incorrect to try to introduce the cate gories of one language into another, typologically distant, language. Usually, both studied languages behave rather differently in this sphere and the problem of aspect must therefore be resolved at text level.